Regulation and targeting of androgen receptor nuclear localization in castration-resistant prostate cancer - Lv, Shidong; Song, Qiong; Chen, Guang; Cheng, Erdong; Chen, Wei; Cole, Ryan; Wu, Zeyu; Pascal, Laura E.; Wang, Ke; Wipf, Peter; Nelson, Joel B.; Wei, Qiang; et al. (The Journal of Clinical Investigation, 2021)
Nuclear localization of the androgen receptor (AR) is necessary for its activation as a transcription factor. Defining the mechanisms regulating AR nuclear localization in androgen-sensitive cells and how these mechanisms are dysregulated in castration-resistant prostate cancer (CRPC) cells is fundamentally important and clinically relevant. According to the classical model of AR intracellular trafficking, androgens induce AR nuclear import and androgen withdrawal causes AR nuclear export. The present study has led to an updated model that AR could be imported in the absence of androgens, ubiquitinated, and degraded in the nucleus. Androgen withdrawal caused nuclear AR degradation, but not export. In comparison with their parental androgen-sensitive LNCaP prostate cancer cells, castration-resistant C4-2 cells exhibited reduced nuclear AR polyubiquitination and increased nuclear AR level. We previously identified 3-(4-chlorophenyl)-6,7-dihydro-5H-pyrrolo[1,2-a]imidazole (CPPI) in a high-throughput screen for its inhibition of androgen-independent AR nuclear localization in CRPC cells. The current study shows that CPPI is a competitive AR antagonist capable of enhancing AR interaction with its E3 ligase MDM2 and degradation of AR in the nuclei of CRPC cells. Also, CPPI blocked androgen-independent AR nuclear import. Overall, these findings suggest the feasibility of targeting androgen-independent AR nuclear import and stabilization, two necessary steps leading to AR nuclear localization and activation in CRPC cells, with small molecule inhibitors.